Modified strip tillage blades for two-wheel tractor seed drills improves maize crop establishment under conservation agriculture. (2021) - Hoque, Muhammad Arshadul; Gathala, Mahesh K.; Hossain, Md Mosharraf; Ziauddin, A.T.M.; Krupnik, Timothy J.
Abstract: Two-wheel tractors (2WTs) are widely used by resource-poor farmers to prepare land in the Eastern Indo-Gangetic Plains (EIGP). This paper demonstrates that improved tillage blade design can enhance maize crop establishment under strip tillage, which falls under the rubric of conservation agriculture (CA). In order to achieve this aim, it is necessary to identify appropriate blade design and rotational speed for power tiller operated seeders, or PTOS, which can be attached to 2WTs and that are increasingly popular in the EIGP. We conducted experiments over two years in two locations in the EIGP within Bangladesh with loam and clay loam soils, respectively. Four blades designed with varying tip angles and five levels of rotational speed were compared with commercially available C-shaped blades sold with 2WTs. Torque and power requirements for strip tillage decreased with decreasing blade tip angle and rotational speed. The best combination of blade design and rotational speed was found with a 15° blade tip angle at 320 RPM. This combination resulted in higher furrow cross sectional area, more soil backfill with appropriately sized soil aggregates, and better seeding depth than C-shaped and 45° tip angle blades. These characteristics also facilitated improved crop establishment on both soil types. Our results indicate that strip-till maize establishment can be improved in Bangladesh by substituting commercially-available C-shaped blades with a 15° blade tip angle at appropriate 320 RPM, though machinery operators will require educational efforts to learn how to fine-tune RPM to improve crop establishment and achieve more sustainable crop establishment systems. Highlights: Significant highlights of this research: Increase potential use of 2WTs in conservation agriculture-based crop production in Eastern Gangetic Plains. Reduce in torque and power requirement of strip tillage seeders. Improve in furrow backfill, uniform seed depth and better crop establishment. Increase conservation agriculture adoption by smallholders.